Cadre Training Without Institutional Transformation: Women's Electability in PDI Perjuangan, Semarang - Fazsya Khalia; Kushandajani; Karebeth Wahyu Firmansyah (Department of Government Studies, Faculty of Social and Political Sciences, Universitas Syiah Kuala, 2026)
Women's representation in Indonesia's legislative bodies remains low despite the implementation of affirmative action regulations in the form of a 30 percent quota for two decades. This study examines how the PDI Perjuangan's women's cadre program contributes to the election of female legislators in the Semarang City Council for the 2024–2029 term. Using a qualitative single case study design, data were collected through in-depth interviews with ten key informants and analysis of party statutes and bylaws. Findings show that cadre development strengthens the technical capacity, internal legitimacy, and mass base of female cadres, but the gap between the output of cadre development and actual election remains persistent. Three structural factors on the demand side elite patronage practices, the command system, and gender-blind nomination policies limit the conversion of political capacity into electoral election. This study confirms that in gender-oriented party institutions, strengthening the supply side will not result in proportional representation without simultaneous institutional transformation on the demand side.